2021
DOI: 10.3390/cells10020403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Browning Agents on the White Adipogenesis of Bone Marrow Mesenchymal Stromal Cells: A Contribution to Fighting Obesity

Abstract: Brown-like adipocytes can be induced in white fat depots by a different environmental or drug stimuli, known as “browning” or “beiging”. These brite adipocytes express thermogenin UCP1 protein and show different metabolic advantages, such as the ability to acquire a thermogenic phenotype corresponding to standard brown adipocytes that counteracts obesity. In this research, we evaluated the effects of several browning agents during white adipocyte differentiation of bone marrow-derived mesenchymal stromal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Even though the present findings were made in an animal model and the clinical validation of CL316243 requires further studies, mirabegron, a β3-adrenoceptor agonist, has been approved for the treatment of overactive bladder symptoms ( Blais et al, 2016 ; Kelleher et al, 2018 ). Besides, PPAR gamma agonist rosiglitazone and sildenafil that acts via a nitric oxide-cyclic guanosine monophosphate pathway, which are known as drugs for the treatment of diabetes and erectile dysfunction respectively, were reported to promote expression of genes associated with browning of WAT ( Mohanty et al, 2004 ; Lefterova et al, 2008 ; Johann et al, 2018 ; Di Maio et al, 2021 ). Thus, following further investigations, CL316243 or other promising browning inducers mentioned above might be useful for the stimulation of fat graft browning, with the aim of improving early revascularization and long-term fat graft retention and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the present findings were made in an animal model and the clinical validation of CL316243 requires further studies, mirabegron, a β3-adrenoceptor agonist, has been approved for the treatment of overactive bladder symptoms ( Blais et al, 2016 ; Kelleher et al, 2018 ). Besides, PPAR gamma agonist rosiglitazone and sildenafil that acts via a nitric oxide-cyclic guanosine monophosphate pathway, which are known as drugs for the treatment of diabetes and erectile dysfunction respectively, were reported to promote expression of genes associated with browning of WAT ( Mohanty et al, 2004 ; Lefterova et al, 2008 ; Johann et al, 2018 ; Di Maio et al, 2021 ). Thus, following further investigations, CL316243 or other promising browning inducers mentioned above might be useful for the stimulation of fat graft browning, with the aim of improving early revascularization and long-term fat graft retention and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophy of adipocytes induces a state of chronic inflammation that causes changes in the brain by inducing neuroinflammation. For instance, some studies have shown that inflammatory processes, especially in the hypothalamus, often follow high-fat feeding [ 15 , 108 , 109 ]. Moreover, chronic low-grade inflammation alters the blood-brain barrier (BBB) due to endothelial dysfunction, generating neuroinflammation and increasing oxidative stress, often resulting in cognitive impairment [ 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PPARα stimulates the transcription of genes that promote mitochondrial biogenesis and mitochondrial oxidation of fatty acids and ketogenesis, increases apolipoproteins A-I and A-II and increases HDL cholesterol levels [ 39 ]. PPARα also stimulates hepatic production of Fibroblast Growth Factor 21 (FGF21) [ 62 ], which increases adiponectin production by adipocytes that, in turn, stimulates AMPK activity in liver and other tissues [ 62 , 63 ]. AMPK also stimulates PPARγ coactivator-1a (PGC-1a) activity, which acts as a coactivator for PPARα [ 61 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%